Impact of poly(A)-tail G-content on Arabidopsis PAB binding and their role in enhancing translational efficiency - Taolan Zhao; Qing Huan; Jing Sun; Chunyan Liu; Xiuli Hou; Xiang Yu; Ian M. Silverman; Yi Zhang; Brian D. Gregory; Chun-Ming Liu; Wenfeng Qian; Xiaofeng Cao (Genome Biology, 2019)
Abstract Background Polyadenylation plays a key role in producing mature mRNAs in eukaryotes. It is widely believed that the poly(A)-binding proteins (PABs) uniformly bind to poly(A)-tailed mRNAs, regulating their stability and translational efficiency. Results We observe that the homozygous triple mutant of broadly expressed Arabidopsis thaliana PABs, AtPAB2, AtPAB4, and AtPAB8, is embryonic lethal. To understand the molecular basis, we characterize the RNA-binding landscape of these PABs. The AtPAB-binding efficiency varies over one order of magnitude among genes. To identify the sequences accounting for the variation, we perform poly(A)-seq that directly sequences the full-length poly(A) tails. More than 10% of poly(A) tails contain at least one guanosine (G); among them, the G-content varies from 0.8 to 28%. These guanosines frequently divide poly(A) tails into interspersed A-tracts and therefore cause the variation in the AtPAB-binding efficiency among genes. Ribo-seq and genome-wide RNA stability assays show that AtPAB-binding efficiency of a gene is positively correlated with translational efficiency rather than mRNA stability. Consistently, genes with stronger AtPAB binding exhibit a greater reduction in translational efficiency when AtPAB is depleted. Conclusions Our study provides a new mechanism that translational efficiency of a gene can be regulated through the G-content-dependent PAB binding, paving the way for a better understanding of poly(A) tail-associated regulation of gene expression.